PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN ROKAN HILIR - Rifardi, Dhandia; Afandi, Dedi; D, Fauzia Andrini (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTThe successfulness of a doctor in giving health services are based on how they applied Indonesian Medical Codes of Ethics or Kode Etik Kedokteran Indonesia (KODEKI) everyday. In January 1st 2014, Jaminan Kesehatan Nasional or National Health Coverage (NHC) started and applied gatekeeper concept for the general practitioner in primary healthcare facilities. By this program, the general practitioners have to give services for the patients that have grown in number in FKTP (primary healthcare facility) maximally. This program has been applied in Indonesia including in Rokan Hilir Regency. The purpose of this research was to know the implementation of KODEKI in NHC’s era in Rokan Hilir Regency. This research used the design of exploration method with qualitative approach. The sample was selected by using snowball sampling method. There were four general practitioners who suited the inclusion’s criterias and willing to be interviewed. The interview was done by the researcher with question’s lists and was recorded by audio recorder. The result of this research showed that the general practitioners in NHC’S era in Rokan Hilir Regency possess altruism, responsibility, professional idealism, accountability, scientific integrity, and social integrity. The results was not only seen from the informants’statements but also their attitude while giving services in publicKeywords : KODEKI values, NHC, Rokan Hilir Regency.